Chitosan Crosslinking from Clam Shells (Cerithidea obtusa) with Tripolyphosphate for Cadmium (II) Adsorption - Soerja Koesnarpadi; Hajar Anuar; Nanang Tri Widodo; Budi Hastuti; Saptono Hadi (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
The study investigates chitosan crosslinking from clam shells (Cerithidea obtusa) with tripolyphosphate for cadmium (II) adsorption. Chitosan was prepared by deacetylating chitin using 60% NaOH and heating at 140°C for 60 minutes. Chitin was isolated from Cerithidea obtusa shells, an abundant waste in East Kalimantan. Crosslinking of chitosan with tripolyphosphate was synthesized via gelation methods, dissolving 5 g of chitosan in acetic acid and adding 0.1% tripolyphosphate as a crosslinker. The chitosan-tripolyphosphate characterization was conducted using FTIR, XRD, and SEM. FTIR spectra revealed an N-H vibration at 1635 cm−1, NH3+ deformation at 1534 cm−1, C-O stretching at 1072 cm−1, and P-O vibration at 1026.91 cm−1, indicating the presence of tripolyphosphate in chitosan. The XRD pattern showed broad peaks at 19.85° and 23.50°, characteristic of amorphous chitosan-tripolyphosphate. SEM images depicted a flat sheet without pores and a tight surface. Cadmium (II) adsorption on chitosan-tripolyphosphate at an optimum pH of 4 followed a pseudo-second-order kinetic model. It adhered to the Langmuir isotherm model, with a maximum adsorption capacity of 27.8 mg/g. The results demonstrate that chitosan crosslinked with tripolyphosphate effectively for cadmium (II) adsorption.